Acceso al crédito e informalidad: análisis a nivel departamental en el Perú 2012-2019 - Manyari Quispe, Katty Emily (2023)
The present study aims to evaluate the direct incidence of access to credit on the levels of informality in the departments of Peru during the period 2012-2019. To do this, the informality rate is used, measured by the "informal situation" variable from the ENAHO "Employment" module, and access to credit, which has financial deepening as a proxy and is measured by the total ratio of direct loans divided by the total GDP by department. Regressions were performed on a panel data model specifying fixed effects. The results indicate that there is a negative effect of 0.12 percentage points in the relationship between access to credit and informality in the departments of Peru. This finding evidenced the heterogeneity of the country’s regions on the variability of access to credit. The econometrics estimation includes regional control variables related to age, superior education, agricultural sector, poverty, company size, independent working women and level of government management. The level of age and government management, as well as the agricultural sector, would not be related to informality, which is a finding contrary to the literature.